THE QUALITY PERFORMANCE OF INTENSIVE ENGLISH COURSE LECTURER - Widya Syafitri (Universitas Mahaputra Muhammad Yamin, 2023)
Intensive English Course (IC) has been considered an essential program to prepare qualified English Department students in higher education in the first semester. The lecturers teach this program for the four skills and two components; listening, reading, speaking, writing, vocabulary and grammar in an integrated manner for one semester. This course will be a success if the lecturers have the capability in content and pedagogy to teach the IC program. Furthermore, this study aimed at describing lecturers’ quality performance in teaching IC at UIN Sjech M. Djamil Djambek (SMDD) Bukittinggi. The data was collected by distributing a questionnaire to 95 first-semester English department students in the 2022/2023 academic year. The findings showed the lecturers’ average was 58,83. It means that the lecturers were qualified in teaching Intensive English Courses in all indicators; tangible, reliability, responsiveness, assurance, and empathy.